Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Number: 4
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

Les mesures d'austérité et les femmes: analyse des documents budgétaires depuis novembre 2008 - Couturier, Eve-Lyne; Tremblay-Pépin, Simon; Institut de recherche et informations socio-économiques (IRIS, 2015)
Contrairement à ce que défend le gouvernement du Québec, celui-ci mène actuellement des politiques d'austérité. Ces politiques ont croisé un certain nombre de mesures de relance que le Québec a tenté d'établir depuis la crise de 2008, mais il n'en demeure pas moins que les compressions ont été plus importantes que les investissements. Cette étude montre que si les mesures de relance ont d'abord favorisé les hommes, les mesures d'austérité, quant à elles, ont surtout affecté les femmes. Ces dernières se trouvent donc doublement perdantes vis-à-vis des mesures instaurées par le gouvernement québécois depuis la crise. Si elle diffère en termes de degré, cette situation correspond à celle qu'on a pu observer en Europe lors de la mise en place de mesures d'austérité.
disponible gratuitement à https://iris-recherche.qc.ca/wp-content/uploads/2021/03/Femmes_et_austerite_WEB.pdf
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; austérité; canada; capitalisme; cours; discipline; histoire et politique; inégalités; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; sofia; systèmes d'oppressions; thématiques; travail; violences

“It Happened More Than Once”: Freezing Deaths in Saskatchewan - Razack, Sherene (Canadian Journal of Women and the Law, 2014)
Le présent article analyse les enquêtes et une commission sur des décès par hypothermie en Saskatchewan, au Canada. Il souligne les économies raciales et d’espace liées à ces décès, et il suggère que les relations structurelles propres au colonialisme de peuplement produisent et encouragent les expulsions continues et quotidiennes d’autochtones de la part des colonisateurs, expulsions qui sont inévitablement violentes. La ville coloniale appartient au colonisateur et son occupation est inévitablement récusée par la présence des autochtones dans la ville. L’autochtonité met mal à l’aise, car elle conteste la prétention du colonisateur à la légitimité en remettant en cause une fiction très tenace dans les états coloniaux selon laquelle les peuples autochtones seraient à l’agonie. La pratique qui consiste à repousser les autochtones aux périphéries de la ville vient du besoin des colonisateurs de maintenir les lignes de force des villes coloniales. Aujourd’hui, quand cette pratique est scrutée par le droit, comme ce fut le cas dans l’enquête sur le décès de Neil Stonechild, et dans des enquêtes sur les décès par hypothermie, elle est considérée soit comme le fait de quelques policiers sans vergogne ou encore on la nie carrément. Ce qui demeure dans les registres judiciaires, toutefois, ce sont les économies raciales d’espace dans la ville coloniale et la dévalorisation persistante de la vie autochtone, une dévalorisation que la loi produit et soutient. Dans la première partie, je présente des idées sur les économies raciales et d’espace de la ville coloniale. Dans la deuxième partie, j’étudie le cas du décès de Neil Stonechild, ainsi que la réponse du droit à ce décès, la Commission d’enquête Wright. Dans la troisième partie, j’analyse les enquêtes sur les décès par hypothermie de Rodney Niastus et de Lawrence Wegner, deux jeunes autochtones morts dix ans après Stonechild, et j’explore deux mouvements dans l’espace et le temps : Niastus et Wegner traversant la ville pour trouver la mort dans un champ gelé de la zone nord-ouest, et le cheminement que l’enquête nous invite à faire en nous faisant croire que Niastus et Wegner sont les seuls responsables de leur décès. Dans le panorama des décès d’autochtones en détention en Saskatchewan, y compris en prison, par suicide et à la suite de violents affrontements avec la police, le corps d’un autochtone est un corps qui ne peut être assassiné.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; histoire et politique; hypothermie; justice sociale; meurtre; mort; personnes autochtones; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; violences

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Néo-« développementisme » extractiviste, gouvernements et mouvements sociaux en Amérique latine - Svampa, Maristella (Problèmes d'Amérique latine, 2011)
La situation actuelle en Amérique latine devient contrastée et dérangeante. Elle illustre non seulement le lien persistant entre l’extractivisme néo-« développementiste » et le néolibéralisme, comme au Pérou, en Colombie ou au Mexique, mais aussi entre ce même extractivisme et les gouvernements progressistes dans un contexte de remontée en puissance de l’interventionnisme de l’État. À cette réalité, il faut ajouter la complexité d’une problématique marquée par le caractère multifactoriel des conflits où se mêlent politiques publiques et logiques d’action et de territoire diverses. Pour traiter ces différents aspects, nous mènerons notre analyse en plusieurs temps. Nous nous intéresserons tout d’abord à la pénétration de l’extractivisme dans la région pour décrire, ensuite, quelques avatars de la notion actuelle de développement. Puis, nous nous arrêterons sur les images et les idées élaborées autour de la nature américaine pour rendre compte de la permanence d’un certain imaginaire, en fonction des « avantages comparatifs » dont la région possède aujourd’hui l’usufruit. Dans les deux dernières parties, nous aborderons la question de la nouvelle cartographie des conflits suscités par la mobilisation autour de questions environnementales animée par des organisations indigènes et paysannes ainsi que par les nouveaux mouvements socio-environnementaux. Un de nos objectifs est d’illustrer les caractéristiques actuelles du tournant éco-territorial où viennent converger discours écologiste et matrice indigène et paysanne.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique latine; amériques; approches et analyses; capitalisme; com5170; cours; discipline; environnement; extractivisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Je suis encore sauvage ! ! ! - Vollant, Mali-Jane (Recherches amérindiennes au Québec, 2011)
Texte personnel décrivant les relations d'une famille autochtone à ma terre et leur combat contre un projet d'exploitation minière sur leur territoire.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; environnement; exploitation minière; histoire et politique; justice sociale; militance; pol4105; premier cycle; périodes historiques; québec; régions géographiques; système colonial; systèmes d'oppressions; territoire; thématiques; uashat–mani-utenam; violences; écologie

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Le texte de McKay, M. C. et Benjamin, C. (2010). A vision for fulfilling the indivisible rights of Indigenous women a été donné en lecture au cours POL4105.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Globalization as Racialized, Sexualized Violence THE CASE OF INDIGENOUS WOMEN - Kuokkanen, Rauna (International Feminist Journal of Politics, 2008)
In my article, I suggest that indigenous women are among the hardest hit by economic globalization – the expansion of markets, trade liberalization and cheapening of labour – and that globalization represents a multifaceted violence against indigenous women. I consider this with the help of two examples. First, I discuss the largely ignored case of missing and murdered Aboriginal women in Canada and how the interlocking systems of oppression (colonization, patriarchy and capitalism) are further intensified by globalization. Second, I examine the death of a Hopi woman, Private Piestewa, in the context of militarization, history of colonization and globalization. I analyse these examples in an intersectional framework that reveals the links between colonization, patriarchy and capitalism all of which inform the current processes of globalization.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; armée états-unienne; canada; capitalisme; cours; discipline; féminicide; globalisation; histoire et politique; intersectionnalité; militarisation; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis